Cidadania e política - Segatto, José Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 1999)
O traço marcadamente excludente e autoritário da história brasileira manifesta-se em sua plenitude quando se analisa o processo político-eleitoral e partidário. Revela com nitidez seu caráter antidemocrático e de restrição dos direitos da cidadania. Ao longo da história foram criadas regras e normas institucionais e jurídicas limitando o direito de voto e facilitando a manipulação e a fraude eleitoral.

The most excludent and autoritarian aspect of the Brazilian history can be seen when the elections process, the political parties and their organization are analyzed. The result of this study clearly reveals an antidemocratic characteristic which restricts the rights of the citizen. Through out our history many institutional and legal rules and procedures have been created to limit the right to vote which, in their last instance, made easy the manipulation, the control and the fraude in any election process.
Citizenship and politics
Keywords: Política; cidadania; democracia; eleições; exclusão; manipulação; clientelismo; coerção; patrimonialismo; violência